REPRESENTASI TRAUMA MASA LALU DAN PEMBENTUKAN KEPRIBADIAN TOKOH DASIYAH DALAM NOVEL GADIS KRETEK KARYA RATIH KUMALA: KAJIAN PSIKOANALISIS SIGMUND FREUD - Dwi Cahyani; Elsa Mulya Karlina (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2026)
This study is motivated by the importance of understanding the relationship between traumatic experiences and the formation of a character’s personality in literary works. The purpose of this study is to describe the representation of past trauma and the formation of the character Dasiyah’s personality in the novel Gadis Kretek by Ratih Kumala, based on Sigmund Freud’s psychoanalytic theory. This study employs a qualitative approach using library research. The primary data source is the novel Gadis Kretek by Ratih Kumala, while secondary data was obtained from relevant books, journals, and references. Data collection was conducted through reading, listening, and note-taking, followed by analysis using qualitative descriptive analysis. The results indicate that the representation of Dasiyah’s past trauma is depicted in three forms: trauma resulting from the loss of a loved one, trauma resulting from betrayal and disappointment, and trauma that continues to influence the character’s life. This traumatic experience had a profound impact on Dasiyah’s psychological state and was repressed into her subconscious, as explained in Freud’s psychoanalytic theory. Furthermore, the formation of Dasiyah’s personality is evident through the dominance of the ego, which plays a role in rationally managing inner conflicts, and the superego, which shapes her sense of responsibility, morality, and concern for her family. Thus, past trauma is not only part of the plot but also plays a crucial role in shaping the character of Dasiyah.